ECONOMIC ASSESSMENT OF THE EFFECTIVENESS AND QUALITY OF MANAGEMENT OF MEDICAL ACTIVITIES OF MEDICAL INSTITUTIONS - Mamasolieva Shokhista Abdugapparovna; Abdunazarova Yulduz Ravshanovna; Nizamova Azizabonu Erkinovna (Scholar Express Journals, 2024)
Certainly! Exploring the economic assessment of the effectiveness and quality of management of medical activities within medical institutions unveils a complex interplay between financial performance, operational efficiency, patient outcomes, and strategic decision-making. This in-depth article will dissect the intricacies of measuring economic effectiveness in healthcare management, analyzing key performance indicators, cost-effectiveness, revenue optimization, and the impact of quality management practices on sustainable financial performance within medical institutions.
Keywords: Economic assessment; efficiency; management; strategic decision